2004
DOI: 10.1097/01.sla.0000128301.67780.d7
|View full text |Cite
|
Sign up to set email alerts
|

Practicing Surgeons Lead in Quality Care, Safety, and Cost Control

Abstract: Since 1998, Quality Surgical Solutions, PLLC, has developed simple physician-authored protocols for delivering high-quality and cost-effective surgery that measure up to benchmark institutions. We have discovered wide areas for improvements in surgery by adherence to simple protocols, minimizing death and complications and clarifying cost issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…In the literature we find several examples of multi-institutional outcome registration programs, in which case-mix adjusted data are fed back to those personally involved in the clinical process of diagnosis, treatment planning, surgical intervention and peri-operative care [35,36]. In Europe, the Nordic countries like Norway and Sweden started a ''national audit'' for the surgical treatment of rectal cancer more than 10 years ago.…”
Section: Outcome-based Referralmentioning
confidence: 99%
“…In the literature we find several examples of multi-institutional outcome registration programs, in which case-mix adjusted data are fed back to those personally involved in the clinical process of diagnosis, treatment planning, surgical intervention and peri-operative care [35,36]. In Europe, the Nordic countries like Norway and Sweden started a ''national audit'' for the surgical treatment of rectal cancer more than 10 years ago.…”
Section: Outcome-based Referralmentioning
confidence: 99%
“…In response to the troubling number of hospital errors, many healthcare organizations have undertaken initiatives targeted toward patient safety (Barry and Smith, 2005). In a longitudinal study of surgeons, the development of a patient safety data system identified several process improvement factors (Shively et al, 2004). Redesigning hospital processes for best practices based on competitive benchmarking has emerged as one of the most common approaches (Dolan, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Patients, third-party payers, and government agencies demand it 8-10 ; surgeons have worked diligently to study and improve the quality of surgical care. [11][12][13] Although there have been some initiatives that clearly seem to have improved outcomes for specific operations, such as coronary revascularization, 14-18 their applicability and relevance to the broad spectrum of surgical procedures remains unclear.…”
Section: Discussionmentioning
confidence: 98%